Insights into National Park Governance based on Global Research Trends: A Lesson for Indonesia - Syaprianto, Syaprianto; Fisdian Adni, Dita; Baharuddin, Tawakkal (Indonesian Association for Public Administration, 2024)
National park governance is urgent in preserving the broadness of biodiversity, nature conservation, and supporting the lives of local communities, demanding a sustainable approach based on global knowledge. This research uses bibliometric analysis to get an idea of global research trends on national park governance and take lessons that can be used in Indonesia. This study maximizes the bibliometric analysis approach with Scopus data sources. Analysis tools are also maximized, namely Nvivo 12 Plus and Vosviewer. The main findings of this research indicate that, through global research trends, national park governance needs to be studied in future research. The tendency of use of the term in biodiversity, nature conservation, conservation management, environmental management, and community participation proved this. Understanding this issue helps create possible governance means more effectively and sustainably, which can be an idea for Indonesia. Findings from global research also provide lessons for Indonesia: They tend to encourage adopting the principle, such as adaptive and collaborative governance in addressing these complex challenges. It can flow on the resolution of conflicts, the involvement of local communities, conservation goals, protection for the environment, the empowerment of indigenous communities, policy changes for and participatory bureaucracy, and satisfying local needs and conservation.